Interleukin‐32δ interacts with IL‐32β and inhibits IL‐32β‐mediated IL‐10 production. Issue 23 (26th October 2013) - Kang, Jeong-Woo; Park, Yun Sun; Lee, Dong Hun; Kim, Man Sub; Bak, Yesol; Park, Su Ho; Ham, Sun Young; Yang, Young; Hong, Jin Tae; Yoon, Do-Young
Abstract : There is growing evidence for multifunctional properties of IL‐32. We previously demonstrated that IL‐32β upregulates IL‐10 production through the association with PKCδ. In this study, we examined the effects of other IL‐32 isoforms on IL‐10 production. We found that IL‐32δ decreased IL‐10 production and investigated the inhibitory mechanism of IL‐32δ. We showed that IL‐32δ suppressed IL‐32β binding to PKCδ by interacting with IL‐32β. The inhibitory effect of IL‐32δ on IL‐32β association with PKCδ was further verified by immuno‐fluorescence staining. The co‐localization of IL‐32β and PKCδ around the nuclear membrane was disrupted by IL‐32δ. Our data therefore indicate that IL‐32δ plays an inhibitory role against IL‐32β function, which also suggests that IL‐32 may be regulated by its own isoform. Abstract : IL‐32δ down‐regulates IL‐10 production. IL‐32δ interacts with IL‐32β. IL‐32δ inhibits IL‐32β function by suppressing IL‐32β association with PKCδ.